2022
DOI: 10.3390/jmse10081155
|View full text |Cite
|
Sign up to set email alerts
|

A Realistic and Integrated Model for Evaluating Offshore Oil Development

Abstract: With the rising consumption of oil resources, major oil companies around the world have increasingly engaged in offshore oil exploration and development, and offshore oil resources have accounted for an increasing proportion. Offshore oil engineering projects are capital intensive, and the development of offshore oil fields faces a tough battle, especially in a period of low oil prices. Thus, a comprehensive evaluation model is highly needed to help assess economic benefits and provide meaningful and valuable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…When the extension distance ∆T is fixed, the displacement h required by the piston will increase with the increase in the cutter face angle α. (2) The increase in the tool face angle α will lead to the reduction in the tool cutting torque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the extension distance ∆T is fixed, the displacement h required by the piston will increase with the increase in the cutter face angle α. (2) The increase in the tool face angle α will lead to the reduction in the tool cutting torque.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, offshore oil production has developed rapidly around the world, and more and more offshore oil production facilities have been established [1,2]. However, the life of offshore oil facilities is usually about 20-50 years [3,4], according to the international practice of offshore oil production and development, and those facilities need to be dismantled if there is no other use for offshore oil and gas facilities after decommissioning [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The production and proven reserves of global submarine oil have steadily increased [1]. After investigation, it was found that a quarter of global oil and 45% of exploitable resources are buried on the seabed [2]. Since 2000, submarine oil fields have accounted for 30% of global oil production.…”
Section: Introductionmentioning
confidence: 99%